2001
DOI: 10.1002/ajh.1104
|View full text |Cite
|
Sign up to set email alerts
|

A common mutation in the gene for coagulation factor XIII‐A (VAL34Leu): A risk factor for primary intracerebral hemorrhage is protective against atherothrombotic diseases

Abstract: The role of a common polymorphism in the factor XIII A-subunit gene (FXIII Val34Leu) has been recently investigated as a protective genetic factor against arterial and venous thrombosis. In addition, the less frequent Leu34 allele has been described as a risk factor for intracerebral hemorrhage. We evaluated the prevalence of this polymorphism by PCR in three case-control studies of patients diagnosed as having primary intracerebral hemorrhage (PCH, n = 130), coronary heart diseases (CHD, n = 240; myocardial i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
70
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(78 citation statements)
references
References 27 publications
8
70
0
Order By: Relevance
“…145 These findings were supported by a smaller study from Italy. 129 A more recent study from the United States did not find a protective effect of Leu34 in a limited number of young women with cerebral infarction. 130 Instead, the authors found that the Phe204 allele of factor XIII, which previously has been linked with an increased risk for miscarriage, 102 was associated with a mild increased risk of ischemic stroke.…”
Section: Factor XIII Val34leu Cerebrovascular Disease and Other Assmentioning
confidence: 99%
See 1 more Smart Citation
“…145 These findings were supported by a smaller study from Italy. 129 A more recent study from the United States did not find a protective effect of Leu34 in a limited number of young women with cerebral infarction. 130 Instead, the authors found that the Phe204 allele of factor XIII, which previously has been linked with an increased risk for miscarriage, 102 was associated with a mild increased risk of ischemic stroke.…”
Section: Factor XIII Val34leu Cerebrovascular Disease and Other Assmentioning
confidence: 99%
“…109 Two further studies have reported a protective effect of Leu34 against MI, with similar odds ratios of around 0.6 (Table 3). 128,129 A third study, which investigated acute MI risk in young women, showed a relative risk of 0.8 for the Leu34 allele in this group of patients. 130 Four publications have reported no association between possession of Leu34 and risk of MI.…”
Section: Factor XIII Val34leu and Coronary Artery Diseasementioning
confidence: 99%
“…However, the role of this polymorphism in ICH is still controversial. Previous reports found that the 34Leu allele predisposes individuals to an increased risk for PICH in an Italian cohort (OR=1.70) [103] . In addition, fibrinogen concentration was found to modify the effect of the polymorphism, such that carriers of the 34Leu allele with a high concentration of fibrinogen may be at risk of hemorrhage [104] .…”
Section: Hemostatic Systemmentioning
confidence: 99%
“…The studies focused on the assumption that the presence of FXIII Leu34 allele might have protective effects against arterial and venous thrombosis [21][22][23]. In a study including 398 patients with acute coronary syndrome and 196 healthy control subjects, it was demonstrated that FXIII Leu incidence was significantly low in the patient group and suggested that this polymorphism was protective against acute coronary syndrome [6].…”
Section: Discussionmentioning
confidence: 99%